Characterization of the Surface Finish of Machined Parts Using Artificial Vision and Hough Transform - Silva, Alberto Rosales; Xeque-Morales, Angel; -Hernandez, L.A. Morales; Funes, Francisco Gallegos (IntechOpen, 2012)
None